Toada do Esquecido & Sinfonia Equestre, de Ricardo Guilherme Dicke: natureza humana e Natureza - Carlos Nogueira (Caravelle)
The last book of the Brasilian writer Ricardo Guilherme Dicke, Toada do Esquecido & Sinfonia Equestre, leads us to think about the relation between the human being, Nature and Environment, as well as about the place of literature in this relationship, in the middle of which are assembled ontological, social, ethical and ecological questions.